2007
DOI: 10.1080/02602930600848267
|View full text |Cite
|
Sign up to set email alerts
|

Work‐based learning assessed as a field or a mode of study

Abstract: Work-based learning is used and assessed in higher education a variety of ways. In this paper we look particularly at the differences between the assessment of WBL when it is constructed as a field of study, i.e., using generic and transdisciplinary criteria and when it is constructed as a mode of study, i.e., when it is assessed using subject specific criteria but the criteria have been met through work-based practice. We draw data from a workshop that took place at a Universities Association for Lifelong Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 6 publications
0
40
0
2
Order By: Relevance
“…Academic practitioners viewed the pedagogy as differing from more discipline-based interpretations of work-related learning and were more conscious of the 'mode' versus 'field of study' WBL debate (Costley and Armsby, 2007) introduced to clarify this range within HE practice. Respondent C identified the importance of the learner as a key characteristic for this perspective: "where government find it rather difficult to get hold of it in policy terms … is talking about the learner… pedagogy, learning philosophy, and this is essential in learner centred learning, absolutely… if it's situated it has to be learner centred."…”
Section: Discipline-centred Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Academic practitioners viewed the pedagogy as differing from more discipline-based interpretations of work-related learning and were more conscious of the 'mode' versus 'field of study' WBL debate (Costley and Armsby, 2007) introduced to clarify this range within HE practice. Respondent C identified the importance of the learner as a key characteristic for this perspective: "where government find it rather difficult to get hold of it in policy terms … is talking about the learner… pedagogy, learning philosophy, and this is essential in learner centred learning, absolutely… if it's situated it has to be learner centred."…”
Section: Discipline-centred Perspectivementioning
confidence: 99%
“…A distinction between the use of the workplace as a 'mode' or a 'field of practice' has been useful to differentiate WBL within HE (Costley and Armsby, 2007), especially among 'newer' forms of WBL that operate outside disciplinary boundaries and in new discursive spaces (Gibbs and Costley, 2006). More recent trends within HE have sought to develop a greater understanding of workforce development (Wedgewood, 2007;Connor, 2005) and define newer practice such as in Hordern's (2013) range of 'workforce development' based on an analysis of 'productive systems'.…”
Section: Work-based Learning Within Hementioning
confidence: 99%
“…The methodologies used in WBL programmes are not specifically different to those that might be used in conventional academic research in similar contexts although there is an understandable tendency to use action based methods. These include problembased learning, action research, action learning, inquiry-based learning, case study, ethnography, cooperative learning, critical thinking and reflective practice (Van Gyn and Grove White 2004;Costley and Armsby, 2007). These are variously apparent in each of the case studies where students are expected to play a more active role in their learning experience, often addressing 'real world' problems and contributing to 'solutions' to be applied in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…This perception of increased responsibility is interesting. Costley and Armsby (2007) found that whilst supervisors may be happy mentoring or training, they often do not see it a part of their role to formally assess.…”
Section: "I Liked the Informal Bit Of Itit Was Good Having It In Mmentioning
confidence: 99%